Designing for engagement: A Realist Synthesis Review of how context affects the outcomes of multi-stakeholder forums on land use and/or land-use change - Sarmiento Barletti, J.P.; Larson, A.M.; Hewlett, C.; Delgado, D. (Elsevier, 2020)
This Realist Synthesis Review (RSR) examines the scholarly literature on multi-stakeholder forums (MSFs) set up to support efforts towards more sustainable land use. In this review, we focus on subnational MSFs that include at least one grassroots and one government actor. MSFs have been presented, especially by practitioners, as a panacea to address land-use change and support climate mitigation, such as through "landscape" or jurisdictional approaches. However, it is not clear that these initiatives are learning from past experience, particularly from research analyzing the effect of context on the ability of such approaches to reach their objectives. To address this gap, the academic literature was assessed using the RSR method to elucidate the key contextual variables affecting outcomes. In addition to analyzing context, this review identifies four common lessons learned for MSFs: the importance of commitment (to the people, the process and its goals); engaging the implementers (key middle level brokers and government officials who determine what happens on the ground); openness to learn from and listen to stakeholders; and having a design that is adaptive to this context, with time and resources to do so. Findings suggest that the most successful MSFs are those that are recognized as part of a wider process that seeks to transform practices at multiple levels; entail a period of research and meetings at upper levels to identify potential roadblocks and existing capacities with those who would implement the project locally; build consensus and commitment from higher levels, and thus political will; and are designed as adaptive learning processes. The central lesson, then, is not one of how to design initiatives, given such different and distinct contexts. Rather, it is about how to design for engagement to address context, whatever its distinct features, in order to develop and implement initiatives with greater chance of success.